The impact of digital technology use on farmers’ low-carbon production behavior under the background of carbon emission peak and carbon neutrality goals - Huang, Xiaohui; Yang, Fei; Fahad, Shah (Frontiers in Environmental Science, 2022)
In the digital economy era, as a new production factor, digital technology can break through the information blocking constraints on farmers' behavior, become an important driving force affecting farmers' low-carbon production behavior, and provide new opportunities for agricultural green low-carbon transformation and the realization of carbon emission peak and carbon neutrality goals. Based on the field survey data of 571 farm households in Jiangsu Province, China, this paper employs the ordered Probit model and the mediating effect test method, and takes risk cognition as the mediating variable to empirically analyze the impact of digital technology use on farmers' low-carbon production behavior and its path. Study results show environmental risk cognition, health risk cognition, agricultural product safety risk cognition and pesticide residue risk cognition have a significant positive impact on farmers' low-carbon production behavior. Study findings also reveal that on one side, digital technology use has a direct effect on the farmers' low-carbon production behavior, and on the other side, it indirectly affects the farmers' low-carbon production behavior by affecting their risk cognition, that is, risk cognition plays a partial mediation role in this relationship. Furthermore, the results indicate that among the control variables, joint cooperative membership, food security cognition, agricultural income, technical guidance, and following instructions have a significant and positive impact on farmers' low-carbon production behavior. Based on study findings, the variable "number of the labor force" has a negative and significant impact on farmers' low-carbon production behavior. Based on study findings, in order to effectively realize carbon emission peak and carbon neutrality goals and promote the sustainable and high-quality development of agriculture, in the process of agricultural policy-making should pay attention to the role of digital technology to actively promote farmers' low-carbon production behavior.